2006
DOI: 10.1016/j.pcrj.2006.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Professional and patient attitudes to using mobile phone technology to monitor asthma: questionnaire survey

Abstract: SummaryAims: There is increasing international interest in using emerging technologies to enhance chronic disease management. We aimed to explore the attitudes of patients and primary care professionals to using mobile technology in order to monitor asthma. Methods: A piloted questionnaire containing closed and open-ended questions assessing attitudes to using electronic self-monitoring was posted to a random sample of general practitioners, asthma nurses, and people with asthma (12 years and over) in Lothian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 26 publications
4
53
0
Order By: Relevance
“…20,21 However, much of the technology-based asthma literature pertains to various types of case management, including measures for surveillance to facilitate various formats of outreach care and education. 4,[22][23][24][25] Technology has also been used as a patient compliance feature through an electronic patient alert and dispensing log system utilizing an audio reminder alert. 26 However, at the heart of quality asthma care is the concept of shared decision making, and asthma guidelines strongly promote this concept.…”
Section: Resultsmentioning
confidence: 99%
“…20,21 However, much of the technology-based asthma literature pertains to various types of case management, including measures for surveillance to facilitate various formats of outreach care and education. 4,[22][23][24][25] Technology has also been used as a patient compliance feature through an electronic patient alert and dispensing log system utilizing an audio reminder alert. 26 However, at the heart of quality asthma care is the concept of shared decision making, and asthma guidelines strongly promote this concept.…”
Section: Resultsmentioning
confidence: 99%
“…Patients reported that the texts made them better able to manage and monitor their asthma. In another study, 9 participants indicated that they found mobile phone technology empowering; however, some wondered if this approach might engender dependence on reminders [28].…”
Section: Introductionmentioning
confidence: 99%
“…Those of which we are aware have also found limited enthusiasm for these methods [7,12,13]. However, studies that have examined the acceptability of these new methods after the patients have used them have reported greater acceptability [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…This may be because they are not familiar with them [7,8] because they miss the human interaction with a doctor or nurse [9,10], or because they are concerned about their privacy and the security of the data [9,11]. How comfortable patients initially feel about using these new methods is likely to affect their willingness to use them, and consequently to create a potential barrier to the implementation of these innovations into routine practice [10].…”
Section: Introductionmentioning
confidence: 99%